Factors influencing the adoption of climate change adaptation strategies in the arid Morocco’s rangelands - Snaibi W. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The high plateaus of eastern Morocco (HPEM) have already suffered the adverse impacts of climate change (CC) since it is at the basis of many of socio-economic and environmental transformations observed in this pastoral ecosystem. Moreover, breeder’s decision to opt for a particular adaptation strategy among a range of possible choices is dependent on certain factors, which need to be known as they will provide indications of factors that favor or hinder adaptation and they are very useful in developing policies to promote effective and successful adaptation. The objective of this study is to identify the factors influencing the adoption of the main endogenous adaptation strategies. Data obtained through a structured questionnaire from 167 herders selected randomly in the HPEM, were analyzed using binary logistic regression. The main determinants of the adoption of climate change adaptation strategies are perceptual and socio-economic variables. The results of the regressions show that the factors significantly influencing the adoption include perception of long-term change of temperature and rainfall, age of head of pastoral household, education level, training received, size of the flock of sheep, equipment in possession and credit access. Thus, in order to enhance local climate change adaptation, it is suggested to take into consideration these above-mentioned determinants, particularly by setting up some accompanying measures (information, training, financing, equipment).
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)